Synthesis of novel chitosan-based flocculants with amphiphilic structure and its application in sludge dewatering: Role of hydrophobic groups. (10th March 2020) - Liu, Yongzhi; Zheng, Huaili; Sun, Yongjun; Ren, Jie; Zheng, Xinyu; Sun, Qiang; Jiang, Shaojie; Ding, Wei
Abstract: Natural polymeric flocculants as sludge conditioners have received great attention due to their non-toxic and biodegradable advantages. However, the application of amphiphilic natural flocculants as sludge conditioners is rarely reported. In this work, the novel chitosan-based flocculants (CS-g-PAO) with amphiphilic structure were synthesized by ultraviolet light initiated method for the enhancement of sludge dewatering performance. The solubility of CS-g-PAO was significantly improved in a wide pH range (2.0–10.0). Various characterization methods were used to investigate the structure, thermal stability and surface morphology of copolymers, suggesting the successful synthesis of CS-g-PAO. In dewatering experiments, CS-g-PAO showed superior dewatering performance, and filter cake moisture content could be decreased to 77.98% from 95.14%. Moreover, the results of extracellular polymeric substances (EPS) components indicated that hydrophobic effect of CS-g-PAO was beneficial to remove the protein in S-EPS and TB-EPS, which had the crucial influence on dewatering performance. Furthermore, the dewatering mechanism was discussed based on the effects of zeta potential, apparent viscosity, surface tension and flocs structure on dewaterability. Results revealed that CS-g-PAO had strong hydrophobic association effect and surface activity. In addition, enhanced charge neutralization and hydrophobic interaction played a synergetic role in improving the dewaterability of CS-g-PAO. Graphical abstract: Image 1 Highlights: A novel chitosan-based flocculant with amphiphilic structure was synthesized. The water solubility of the amphiphilic flocculant was improved in a wide pH range. The amphiphilic flocculant showed superior dewatering efficiency under low dosage. All results confirmed the role of charge neutralization and hydrophobic attraction.